The Measurement of the Reflection and Transmission Properties of Conducting Fabrics to Milli-Metric Wave Frequencies - Alabaster, Clive M.; Oxley, C.; Williams, J.; Hopper, R.; Flora, H.; Eibeck, H. (Cranfield University, 2007)
There is increasing interest in conducting fabrics and their uses at RF and microwave frequencies. This paper for the first time looks at the reflection and transmission measurements of bobbinet and knitted materials from around 8GHz into the milli-metric frequency range 110GHz, where the material geometry is comparable to the wavelength of the wave. Bobbinet materials were found to behave like lossy dielectrics and may be useful in the construction of thin light-weight screening and absorption planes. While the knitted materials, with very small mesh geometry, gave a reflection coefficient which was comparable to a metal foil.